Emerging Roles of Coronavirus in Autoimmune Diseases - Zhou, Si-Yu (Arch Med Res, 2021)
Virus infection can alter immune regulatory activity, and thus may be involved in the occurrence of autoimmune diseases. Recently, the pandemic of COVID-19 has posed a huge threat to public health and emerging evidence suggests that coronavirus may be implicated in the development and pathogenesis of autoimmune diseases. However, how coronavirus infection impacts the risk of autoimmune disease remains largely unknown. In this review, we focused on the association between coronavirus and autoimmunity, and elucidated the molecular mechanisms linking coronavirus exposure to autoimmunity. Additionally, we briefly introduced the role that coronavirus plays in several autoimmune diseases including multiple sclerosis (MS), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and idiopathicthrombocytopenic purpura (ITP).